Fibroma: case report - Sabino, Natalia Aline Ricci; Gaetti-Jardim, Ellen Cristina; Gaetti-Jardim Jr, Elerson; de Melo, Rosana Leite (ARCHIVES OF HEALTH INVESTIGATION, 2016)
Fibroma is a common injury in the oral mucosa, considered a reactive hyperplasia of connective tissue in response to constant trauma to the oral mucosa is dental order or not, is a noninfectious lesion benign fibrous connective tissue, with a predilection for females and between the fourth and sixth decades of life and are usually situated in the inner portion of the lower lip, tongue and buccal mucosa. They are usually nodular, firm palpation, asymptomatic and coloring similar to the adjacent mucosa, sessile base, smooth surface. Routine treatment is conservative surgical excision. This paper reports a clinical case of irritation fibroma in the oral mucosa of large patient ratios male, young and constant trauma history in the region, as well as dental crowding near pathology. Such fibroma was treated surgically and with remission of awareness of the deleterious habits oral mucosa to prevent the recurrence of the lesion. Descriptors: Fibroma; Diagnosis; Therapeutics.